Designing the future of healthcare together: prototyping a hospital co-design space. Issue 4 (2nd October 2017) - Reay, Stephen; Collier, Guy; Kennedy-Good, Justin; Old, Andrew; Douglas, Reid; Bill, Amanda
Abstract: This paper contextualises the emergence and continuing development of the Design for Health and Wellbeing (DHW) Lab, a collaboration between a university and a hospital in Auckland, New Zealand. The DHW Lab was established with the vision of creating a design space in which designers, students, patients and hospital staff could work together to identify and address contemporary healthcare issues in innovative ways. In this paper, we explain how the continuing development of the space reflects the design principles it espouses, and how this is embedding design principles and practices into a healthcare organisation. In particular, we will show how the users of the space contribute to the evolution of its physical appearance, its values and its performance as they come to identify and make sense of the challenges, possibilities and potential of the DHW Lab initiative.